CTLA-4 Polymorphisms in Patients with IgA Nephropathy Correlate with Proteinuria - Marius Jacob; Kim Ohl; Tannaz Goodarzi; Sigrid Harendza; Thomas Eggermann; Christina Fitzner; Ralf-Dieter Hilgers; Anna Bolte; Jürgen Floege; Thomas Rauen; Klaus Tenbrock (Karger Publishers, 2018)
Background/Aims: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis and still constitutes one of the most important causes of end-stage renal disease. Abnormal T cell responses may play a role in IgAN pathogenesis. Co-stimulatory molecules such as cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) are important for naive T cells to initiate and terminate immune responses. Single nucleotide polymorphisms (SNPs) in the CTLA4 gene locus are associated with several autoimmune diseases. Methods: We aimed to investigate the occurrence of the SNPs -318C/T, +49A/G and CT60 G/A within the CTLA4 locus in healthy blood donors (n=455) and IgAN patients (n=252) recruited from the recently published STOP-IgAN trial. The presence of these SNPs was then associated with baseline proteinuria in IgAN patients. Results: We observed a significantly increased frequency of the CTLA4 -318C/T genotype in IgAN patients as compared to controls (CC vs. CT+TT: OR 1.65, 95%-CI 1.03-2.65, p=0.035). No significant associations, neither with the +49A/G nor for the CT60 G/A SNP, were detected. However, when we stratified for proteinuria at time of inclusion into the STOP-IgAN trial (<1 g/day vs. >1 g/day), we observed significant differences in the frequencies of the CT60 G/A genotype, i.e. a significantly increased risk for higher proteinuria in patients carrying the G allele (OR 2.81, 95%-CI 1.03-7.64, p=0.042). Conclusion: The CTLA4 -318/C/T SNP was associated with an increased risk to develop IgAN, while the CT60 G/A genotype significantly associated with the risk for higher proteinuria suggesting a possible role for CTLA-4 in IgAN.